Millennial Public Speaking Training (Pelatihan Public Speaking untuk Kalangan Remaja) - Rohendi, Rohendi; Muzzammil, Faisal (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2022)
The rapid flow of information and the free flow of communication on social media has a negative impact on today's millennial generation. The negative impact due to excessive and inappropriate use of social media is the reduction in social interaction and communication among adolescents. Based on the background of the problem regarding the declining communication skills and skills of the current millennial generation, it is necessary to carry out public speaking training activities for the millennial generation, including for teenagers in Purwakarta Regency. This public speaking training activity for youth in Purwakarta Regency has two main objectives, namely: (1) To provide conceptual knowledge about public speaking; (2) Improving practical skills about public speaking. This public speaking training activity is carried out using two methods, namely: (1) Public Speaking Sharing; (2) Public Speaking Training. Based on the implementation of the public speaking training activities, the result is that this public speaking training can build and improve communication skills for youth.